2017
DOI: 10.1021/acs.inorgchem.6b03057
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MAX Phases in the Zr-Ti-Al-C System

Abstract: This study reports on the synthesis and characterization of MAX phases in the (Zr,Ti)AlC system. The MAX phases were synthesized by reactive hot pressing and pressureless sintering in the 1350-1700 °C temperature range. The produced ceramics contained large fractions of 211 and 312 (n = 1, 2) MAX phases, while strong evidence of a 413 (n = 3) stacking was found. Moreover, (Zr,Ti)C, ZrAl, ZrAl, and ZrAl were present as secondary phases. In general, the lattice parameters of the hexagonal 211 and 312 phases foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 37 publications
(69 reference statements)
1
60
0
4
Order By: Relevance
“…An alternative approach to obtain MAX phase pure material is to stabilize this stoichiometry by making (Zr, M) 2 AlC and Zr 2 (Al, A)C solid solutions 11 . Stable solid solutions on the M-site have been reported for M = Nb and Ti 1214 , while recently the in-plane ordered (V 2/3 , Zr 1/3 ) 2 AlC i-MAX phase was synthesized 15 . Horlait et al .…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to obtain MAX phase pure material is to stabilize this stoichiometry by making (Zr, M) 2 AlC and Zr 2 (Al, A)C solid solutions 11 . Stable solid solutions on the M-site have been reported for M = Nb and Ti 1214 , while recently the in-plane ordered (V 2/3 , Zr 1/3 ) 2 AlC i-MAX phase was synthesized 15 . Horlait et al .…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 4b 42,45 Our theoretical results indicate that disorder is preferred, though a more in-depth discussion of these discrepancies will be presented below.…”
Section: Order and Disorder In Quaternary 312 Max Phasesmentioning
confidence: 87%
“…17,48 We have previously shown that o-MAX phases can be stable both upon limited intermixing of M′ and M″, and at off-stoichiometries. 15,24 Ti 2 ZrAlC 2 or (Ti 0.67 Zr 0.33 ) 3 AlC 2 is another example where both order 45,49 and disorder 42,51 have been claimed. Our results indicate that Ti and Zr prefer disorder or possibly semi-order, based on the moderate T disorder = 357 K combined with a similar electronegativity of Ti and Al.…”
Section: The Origin Of Out-of-plane Chemical Order and Disorder In Mamentioning
confidence: 99%
“…Another alternative is to use metal hydrides, such as TiH 2 or ZrH 2 , 142 since they seem to be beneficial for compositions that are difficult to synthesize such as Zr 2 AlC or Zr 3 AlC 2 . 143,144 However, the use of metallic hydrides might be dangerous because of the liberation of H 2 during the thermal process, so safety has to be strongly considered for large quantities. As "A" source, elemental powders such as Al or Si are extensively used due to the low prices, and an excess up to 20 at.…”
Section: Liquid/solid State Reactionmentioning
confidence: 99%